2006
DOI: 10.1148/radiol.2392050075
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pulmonary Embolism:Pulmonary Artery Clot Load Scores and Cardiovascular Parameters as Predictors of Mortality

Abstract: Purpose:To retrospectively evaluate pulmonary artery (PA) clot load scores and computed tomographic (CT) cardiovascular parameters as predictors of mortality in patients with severe pulmonary embolism (PE). Materials and Methods:Institutional review board approval was obtained with waiver of informed consent. A total of 82 consecutive patients (42 women, 40 men; mean age Ϯ standard deviation, 61 years Ϯ 15) were admitted to the intensive care unit for PE-related conditions and were evaluated by using CT pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
143
5
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 233 publications
(182 citation statements)
references
References 45 publications
27
143
5
7
Order By: Relevance
“…Several previous studies have suggested that pulmonary arterial embolic burden assessed by CT as well as by RV/LV ratio is also a predictor for APTE patients (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). On the other hand, Ghaye et al (19) suggested that RV/LV diameter ratio and azygos vein diameter were significant predictors, and that pulmonary arterial embolic burden was not.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Several previous studies have suggested that pulmonary arterial embolic burden assessed by CT as well as by RV/LV ratio is also a predictor for APTE patients (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). On the other hand, Ghaye et al (19) suggested that RV/LV diameter ratio and azygos vein diameter were significant predictors, and that pulmonary arterial embolic burden was not.…”
Section: Discussionmentioning
confidence: 98%
“…According to the past literatures (14)(15)(16)(17)(18)(19)(20), the scans were evaluated by measuring the minor axes of the right and left ventricles of the heart in the transverse plane at their widest points between the inner surface of the free wall and the surface of the interventricular septum. These maximum dimensions may be found at different levels.…”
Section: Contrast-enhanced Ctmentioning
confidence: 99%
See 3 more Smart Citations